Variability studies in papaya (Carica papaya L.) - Reshma, N. T.; Babylatha, A. K.; Radha, T. (Journal of Tropical Agriculture, 2017)
Systematic collection of forty papaya types was done out in central zone of Kerala to assess the variability in respect of morphological, flowering, fruiting and biochemical characters in papaya. It was observed that wide range of variability exists in papaya grown in the homesteads of Kerala. The plant height of forty collections varied from 2.1 to 6.6 m and collar girth varied from 30.00 to 88.16 cm. Fruit weight and fruit volume of the collections varied from 440 to 3,130 g and 400 to 3,280 ml, respectively. Flesh thickness of the collections ranged from 1.9 to 4.3 cm. Fruits showed variation in flesh colour from light yellow to scarlet. Biochemical analysis indicated that the total soluble solids (TSS) varied from 3.80 0Brix to 14 0Brix.